Community Acceptance of Children with Disabilities in Medan City - Hairani Siregar; Siti Hazzah Nur (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This research is to see how the family and society accept the presence of children with disabilities in the family and society. This research was conducted in Medan Johor District, Medan City. This research uses qualitative research methods with a descriptive approach. Using data collection techniques from interviews, observation, and documentation studies and using qualitative data analysis. The informants in this study were parents who have children with disabilities, communities who have neighbors with children with disabilities, community leaders and the coordinator of children with disabilities in Medan. The results of the research conducted show that parents who have children with disabilities feel very sad at the start of knowing that their children have disabilities and have a great sense of concern for the child's future. As time goes by, parents' acceptance of children with disabilities gets better, especially when parents see children's talents that need to be developed. Family neighbors who have children with disabilities, community leaders are able to accept the presence of children with disabilities present in the midst of the environment. Public. Furthermore, the coordinator of children with disabilities stated that there are still children with disabilities who experience discrimination and there is no forum provided by Medan City Government as a place to practice and channel the talents of children with disabilities.